An upper observable black hole mass scale for tidal destruction events with thermal X-ray spectra - Mummery, A; Balbus, SA (Oxford University Press, 2021)
We comprehensively model the X-ray luminosity emergent from time-dependent relativistic accretion discs, developing analytical models of the X-ray luminosity of thermal disc systems as a function of black hole mass M, disc mass Md, and disc α-parameter. The X-ray properties of these solutions will be directly relevant for understanding tidal disruption event (TDE) observations. We demonstrate an extremely strong suppression of thermal X-ray luminosity from large mass black holes, LX ∼ exp (− m7/6), where m is a dimensionless mass, roughly the black hole mass in unity of 106M⊙. This strong suppression results in upper observable black hole mass limits, which we demonstrate to be of order Mlim ≃ 3 × 107M⊙, above which thermal X-ray emission will not be observable. This upper observable black hole mass limit is a function of the remaining disc parameters, and the full dependence can be described analytically (equation 82). We demonstrate that the current population of observed X-ray TDEs is indeed consistent with an upper black hole mass limit of order M ∼ 107M⊙, consistent with our analysis.